REBEL - Hayden, Tom (Book collections on Project MUSE., 2003)
In Rebel: A Personal History of the 1960s,Tom Hayden, a seminal figure in the civil rights and anti-war movements of the 1960s, documents a period in U.S. history of major social and political change. Including excerpts from FBI files, speeches, and journal entries, Rebel provides wisdom to a new generation for whom the belief in non-violence and social change is as relevant as ever.